Effects of marine protein-, marine oil- and marine-1 free diets on the growth performance and innate immune responses of Atlantic salmon (Salmo salar, L.) post-smolts - Metochis, Christoforos; Crampton, Viv; Ruohonen, Kari; El-Mowafi, Adel; Bell, J Gordon; Adams, Alexandra; Thompson, Kim D (Aquaculture Research, 2017)
Atlantic salmon post-smolts of an average of 940g were fed six diets including two marine-based commercial diets one with partial inclusion of vegetable proteins (VPs) and oils (VOs) (2011/12 EU standards) (MB) and a second with partial inclusion of VPs, land animal-by-product (ABP) proteins and VOs (non-EU standards) (MBABP), a fully vegetable protein (VP) diet; a fully algal and VOs (VO) diet; a fishery-free vegetable-based (VP/VO) diet; and a fishery-free diet with a mix of VPs and ABP proteins and a mix of algal and vegetable oils (MFABP). Growth was assessed at Days 104 and 175, whereas fillet proximate composition, haematology and innate immune responses were assessed upon termination. Overall, MB salmon was the best performing group for the full period in terms of feed intake and overall weight gain. MB and VP salmon exhibited the highest FCRs compared to the other groups, while VP salmon exhibited the highest condition factor (K) and VO salmon the lowestKcompared to the other groups. Fillet proximate composition did not present differences among the six groups. MB salmon demonstrated the highest plasma lysozyme activity compared to the other groups while MFABP, VP and VP/VO salmon demonstrated higher plasma anti-protease activity in contrast to MB salmon. The dietary groups did not present differences in plasma protein, total IgM or natural haemolytic activity while unaltered head kidney macrophage respiratory burst activity was also observed. Overall, diets free from marine proteins or oils and/or both were satisfactorily utilized by salmon without compromising their immune capacity, although longer adaptation periods are required.